The teacher education program of the Marikina School of Arts and Trades implications for Thailand - Chantrkasem, Udomsakdi 1937- (s.n.], 1972)
The teacher education program of the Marikina School of Arts and Trades (MSAT), its curricular content, rules and regulations, and certain practices were analyzed in this study